Intellectual property-A strong determinant of Economic Growth - Love k Singh; Aarti Sharma; Mummun rai (Wolters Kluwer Medknow Publications, 2009)
The returns from almost all human endeavors can ultimately be translated into monetary gains. The past few years have seen increased attention to the strengthening of intellectual property rights due to globalization. The development of Intellectual property rights (IPR) over the years has invariably brought an upsurge in the outlook of nations towards the aspect of societal and cultural growth, this being said with the preliminary assumption that economic growth has been the most affected realm and that it requires a separate spectrum of analysis. The artifacts between the IP regime and the national economy can be easily interpreted by the fact that India’s independence had itself brought an era where the enactment of the national IP laws were considered to stand on the touchstone of the market economy. The aim of the present paper is to investigate the impact of strong IP regime in the economic development of a nation and also a light is raised into Indian economy and creation for an efficient innovating system is discussed. A strong relation of IPR wity pharma sector and biotech sector has been discussed. Undoubtedly, IP systems must be developed so as to bring in socio-economic well-being. The fact that strong IPR actually provoke IPR infringements in many developing nations also seems to be an issue which needs to be analyzed while understanding the need of the former. The trade-off between unfair competition laws and IP also assumes importance of high magnitude and hence needs to be particularly emphasized. With the growing recognition of IPR, the importance of world wide forums on IPR is realized. Companies, universities, and industries want to protect their IPR internationally. In order to reach this goal, countries have signed numerous agreements and treaties.